Has macroeconomic forecasting changed after the Great Recession? Panel-based evidence on accuracy and forecaster behaviour from Germany - Jörg Döpke; Ulrich Fritsche; Karsten Müller (Hamburg University, Department Socioeconomics, 2018)
Based on a panel of annual data for 17 growth and inflation forecasts from 14 institutions for Germany, we analyse forecast accuracy for the periods before and after the Great Recession, including measures of directional change accuracy based on Receiver Operating Curves (ROC).We find only small differences on forecast accuracy between both time periods. We test whether the conditions for forecast rationality hold in both time periods. We document an increased crosssection variance of forecasts and a changed correlation between inflation and growth forecast errors after the crisis, which might hint to a changed forecaster behaviour. This is also supported by estimated loss functions before and after the crisis, which suggest a stronger incentive to avoid overestimations (growth) and underestimations (inflation) after the crisis. Estimating loss functions for a 10-year rolling window also reveal shifts in the level and direction of loss asymmetry and strengthens the impression of a changed forecaster behaviour after the Great Recession.
Keywords: E32; E37; G11; 330; Macroeconomic Forecasting; Forecast Error Evaluation; Germany